FAMILIAL MIGRAINE LIMB PAIN SYNDROME (MLPS): THREE GENERATIONS AND SEVEN YEAR FOLLOW-UP. Issue 11 (14th October 2015) - Angus-Leppan, Heather; Guiloff, Roberto Jaime
Abstract : We describe a family with migraine-limb pain syndrome (MLPS) in children and adults over three generations, in an autosomal dominant pattern. MLPS is intermittent pain occurring in any limb, temporally related to a migraine episode, cluster headache or cluster migraine. It is usually ipsilateral to the headache, but can alternate and may spread with a migrainous march over 20 minutes or more. Body or chest pain (corpalgia) is also described. Limb or body pain may not coincide with headache at presentation. The association may be misdiagnosed as radiculopathy, thoracic outlet syndrome or arthritis. There is one previous report of a family with childhood limb pain, followed by migraine in adulthood, in a pattern suggesting autosomal dominant inheritance. We report a second family with three generations of MLPS starting in childhood or adulthood, with variable duration, commencing in any limb. All the patients with limb pain had concurrent or associated migraine with aura. Pain intensity in the previous family was mild, but poorly responsive to treatment. In our family the symptom was treatment responsive with variable intensity. Convergence of nociceptive input from the trigeminovascular system in the cervical spinal cord, brainstem, thalamus and cortex is a possible physiological basis for MLPS.